Peningkatan Produktivitas Kerja Karyawan Melalui Semangat Kerja - Muliadi Muliadi (LPPM IAIN Sorong, 2019)
Focus of this study is to discuss Employee Productivity Improvement through work spirit. The purpose of this research is to study the impression of the work spirit on increasing employee productivity at the Marisa Unit Prosperous Cooperative in Pohuwato Regency. Research is participatory research, using questionnaires as research instruments and using simple regression analysis. The results showed that the work spirit was positive and significant towards work productivity of 0.569 (56.9%), while 43.1% did not discuss the model or not